Os Abas Largas da Brigada Militar em fotografias: políticas arquivísticas para a preservação e difusão da memória - Skrebsky, Maria Candida da Silveira (2011)
Starting from the assertion that the public archives are important repositories of photo documentary collections in need of technical appropriate treatment, what concerns their organization, description, conservation and release, this is also the case of the photographic collection of the Historical Centre Colonel Pillar (CHCP), cultural military state institution of public nature, subordinate to the 1st Regiment of Mounted Police Rgt. Cel. Pillar (1st RPMon.) of the Military Brigade (BM) of Rio Grande do Sul State. Ahead of such expectations, this research aimed to produce a selective catalogue of photographs to be published in the internet, through the implementation of archivistic politicians classification (arrangement), description, conservation and diffusion in the photographic collection of the CHCP of the period from 1955 to 1974, referring to the acting of the Regiment of Mounted Rural Police officer of the Military Brigade (RPRMont). For its realization there was adopted the approach of case study gone with bibliographical research, documentary research, field work and straight observation, in view of the necessity to know widely and in detail the context of creation of the photographs, it was important to study the history and the activities of the institutions Military Brigade and 1st RPMon.; in special, the period from 1955 to 1974 in which the 1st Regiment acted like Mounted Rural Police officer, as well as to know the reality of the photographic collection of the CHCP, in order to propose the archival treatment appropriate to be employed. As result, it was possible to establish a methodology of archival treatment for photographic collections, in harmony with the theory and normalization of archives, that propitiated the elaboration of the electronic version of the Selective Catalogue of Photographs Wide Brims: elite troops of the Military Brigade" composed of 190 photographic images representing the trajectory of the 1st RPMon. as Regiment of Rural Police officer, which, from then, it became popularly known as Regiment Wide Brim .